Preoperative anxiety management in children. Benefits of humanoid robots: an experimental study - Franconi, Ilaria; Faragalli, Andrea; Palego, Giulia; Canonici, Samuele; Gatti, Ludovica; Simonini, Alessandro; Bindi, Edoardo; Cobellis, Giovanni; Carle, Flavia (Frontiers in Surgery, 2023)
Objective The purpose of this study was to determine whether the use of a humanoid robot (Estrabot) could reduce preoperative anxiety levels in children. Methods An experimental study was conducted at Azienda Ospedaliero Universitaria delle Marche Hospital, involving the Pediatric Surgery ward and the Operating Room (OR). The clinical documentation of patients aged between 2 and 14 years who underwent minor surgery was included. The Instruments used were the Children's Emotional Manifestation Scale to evaluate anxiety levels, and Estrabot, a humanoid robot that interacts with people. Medical records between July 2019 and February 2020 were analyzed and the data was anonymous. The level of anxiety is extrapolated in Pediatric Surgery during the administration of oral pre-medication, and in the Operating Room, during the induction of anesthesia. Patients were divided into an intervention group treated with Estrabot, and a control group without a robot. Results The population consists of 60 patients (86.7%) with a median (IQR) age of 6 (4-8) years The median (IQR) anxiety score during premedication was 7 (5-11), while the median (IQR) anxiety score during anesthesia was 6 (5-10). A significantly lower level of anxiety was reported in the Estrabot group both during oral premedication and anesthesia administration. Patients in the Estrabot group had significantly lower anxiety levels in both age groups (less than 8 years and more or equal to 8 years). Conclusion A humanoid robot can reduce preoperative anxiety levels in children during premedication and the induction of anesthesia.